Numerical Study on the Influence of Length-Diameter Ratio on the Performance of Dynamic Pressure Oil-Air Separator - Xiaobin Zhang; Xiaofeng Zhang; Delin Gu; Lei Lang; Na Gao (International Journal of Chemical Engineering)
In order to study the separation characteristics of the aeroengine dynamic pressure oil-air separator, this paper uses the coupling method of PBM and CFD two-fluid model to study the influencing factors such as cylinder diameter, cylinder length, and other factors on the separator performance. The flow field structure, velocity, gas volume distribution, separation efficiency, and gas and liquid holdup rate in the separator under different operating conditions are analyzed. Combined with the analysis results of the cylinder diameter and the cylinder length, the influence law of length-diameter ratio on separation efficiency is summarized. The optimum length-to-diameter ratio that maximizes the separation performance of the separator is obtained in this research, which provides a reference for the design and improvement of the separator. The results show that, as the diameter of the cylinder increases, the separation efficiency increases first and then decreases. When dsep = 16 mm and dsep = 18 mm, the separator reaches its maximum efficiency, which is about 93%. With the increase of the cylinder length, the separation efficiency first increases and reaches the maximum when l2 = 90 mm and then decreases slowly. When the separator cylinder is either too long or too short, it will cause the separation performance to decrease. There is an optimal aspect ratio. There is an optimal aspect ratio, and the separation performance of the separator is the best when the aspect ratio is between 5 and 6.